2011
DOI: 10.1002/mop.25881
|View full text |Cite
|
Sign up to set email alerts
|

Novel microstrip dual‐band bandpass filter with wide stopband and high isolation

Abstract: A novel microstrip dual‐band bandpass filter (BPF) using spur‐line‐loaded stepped‐impedance resonator (SIR) is proposed in this letter.Anti‐parallel coupled microstrip line is used to realize the dual‐band coupling and produce a transmission zero within two passbands. High isolation between two passbands is achieved. A spur‐line is loaded to the SIR to eliminate the higher spurious frequencies of the resonator. A dual‐band BPF with central frequencies of 2.4 and 5.6 GHz is designed. The designed filter has a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Luo and Deng demonstrated that the size problem can be overcome by combining two sets of independent resonators with common input and output; however, such structures are very complicated. Currently, stepped‐impedance resonators (SIRs) and open‐loop resonators have been extensively investigated due to their attractive features, which could be applied to a dual‐band BPF with a simple structure, nevertheless the selectivity of some circuits remains to be improved. Furthermore, some researchers focus on realizing dual‐band filter with tunable passband ; however, the insertion loss and selectivity are not good and the tunable passband is only single passband.…”
Section: Introductionmentioning
confidence: 99%
“…Luo and Deng demonstrated that the size problem can be overcome by combining two sets of independent resonators with common input and output; however, such structures are very complicated. Currently, stepped‐impedance resonators (SIRs) and open‐loop resonators have been extensively investigated due to their attractive features, which could be applied to a dual‐band BPF with a simple structure, nevertheless the selectivity of some circuits remains to be improved. Furthermore, some researchers focus on realizing dual‐band filter with tunable passband ; however, the insertion loss and selectivity are not good and the tunable passband is only single passband.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as an indispensable part of RF front ends, filters have gained a lot of attention due to the rapid development of modern communication systems, e.g., wireless local area networks (WLAN), global system for mobile communications (GSM), the third generation (3G), the fourth generation (4G), worldwide interoperability for microwave access (WiMax), etc. Due to the demands on working in multiband, the multiband bandpass filters, especially dual-band filters [1][2][3][4], become a hot research issue.…”
Section: Introductionmentioning
confidence: 99%